Proton therapy for head and neck squamous cell carcinomas: A review of the physical and clinical challenges. (June 2020) - Beddok, Arnaud; Vela, Anthony; Calugaru, Valentin; Tessonnier, Thomas; Kubes, Jiri; Dutheil, Pauline; Gerard, Anais; Vidal, Marie; Goudjil, Farid; Florescu, Carmen; Kammerer, Emmanuel; Benezery, Karen; et al.
Highlights: Proton therapy has the potential to reduce the severity of toxicities for head and neck cancers. The optimization of beam delivery and treatment planning can decrease uncertainties. Patient preparation may be different from that for IMRT. Robustness is necessary for improving model-based approaches and randomized trials. Abstract: The quality of radiation therapy has been shown to significantly influence the outcomes for head and neck squamous cell carcinoma (HNSCC) patients. The results of dosimetric studies suggest that intensity-modulated proton therapy (IMPT) could be of added value for HNSCC by being more effective than intensity-modulated (photon) radiation therapy (IMRT) for reducing side effects of radiation therapy. However, the physical properties of protons make IMPT more sensitive than photons to planning uncertainties. This could potentially have a negative effect on the quality of IMPT planning and delivery. For this review, the three French proton therapy centers collaborated to evaluate the differences between IMRT and IMPT. The review explored the effects of these uncertainties and their management for developing a robust and optimized IMPT treatment delivery plan to achieve clinical outcomes that are superior to those for IMRT. We also provide practical suggestions for the management of HNSCC carcinoma with IMPT. Because metallic dental implants can increase range uncertainties (3–10%), patient preparation for IMPT may require more systematic removal of in-field alien material than is done for IMRT. Multi-energy CT may be an alternative to calculate more accurately the dose distribution. The practical aspects that we describe are essential to guarantee optimal quality in radiation therapy in both model-based and randomized clinical trials.